2014
DOI: 10.4236/sgre.2014.51002
|View full text |Cite
|
Sign up to set email alerts
|

Sizing of STATCOM to Enhance Voltage Stability of Power Systems for Normal and Contingency Cases

Abstract: The electric power infrastructure that has served huge loads for so long is rapidly running up against many limitations. Out of many challenges it is to operate the power system in secure manner so that the operation constraints are fulfilled under both normal and contingent conditions. Smart grid technology offers valuable techniques that can be deployed within the very near future or which are already deployed nowadays. Flexible AC Transmission Systems (FACTS) devices have been introduced to solve various po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Estos dispositivos están construidos con elementos estáticos y mediante elementos de electrónica de potencia que, en su conjunto, nos permite mejorar el control y aumentar la capacidad de transferencia de energía en sistemas de corriente alterna (CA). El principio de funcionamiento del compensador sincrónico, que es un tipo de FACTS, opera bajo tres criterios fundamentales i) un condensador de corriente continua (CC) detrás de un transformador opera como una fuente de tensión controlable, ii) la diferencia de tensión en la reactancia del transformador produce intercambios de potencia activa y reactiva entre el STATCOM y el SEP y iii) la magnitud de tensión de salida del STATCOM se puede controlar a través de la variación de tensión que circula por el condensador de CC [19][20][21]. Una estructura básica que resume la arquitectura del STATCOM se ilustra con la Figura 2.…”
Section: Materiales Y Métodosunclassified
“…Estos dispositivos están construidos con elementos estáticos y mediante elementos de electrónica de potencia que, en su conjunto, nos permite mejorar el control y aumentar la capacidad de transferencia de energía en sistemas de corriente alterna (CA). El principio de funcionamiento del compensador sincrónico, que es un tipo de FACTS, opera bajo tres criterios fundamentales i) un condensador de corriente continua (CC) detrás de un transformador opera como una fuente de tensión controlable, ii) la diferencia de tensión en la reactancia del transformador produce intercambios de potencia activa y reactiva entre el STATCOM y el SEP y iii) la magnitud de tensión de salida del STATCOM se puede controlar a través de la variación de tensión que circula por el condensador de CC [19][20][21]. Una estructura básica que resume la arquitectura del STATCOM se ilustra con la Figura 2.…”
Section: Materiales Y Métodosunclassified
“…There are various criteria for determining the required size of STATCOM devices [62] and [63]. STATCOM devices can be sized considering the ratings of the renewable energy systems connected to the gridas presented in [64].…”
Section: Sizing and Placement Of D-statcommentioning
confidence: 99%
“…Where in this study, a STATCOM device was added to the system. Previous studies had reported that the placement criterion of STATCOM is to have it connected at the weakest bus of the system [20]. The weakest bus was identified as bus 14.…”
Section: 11load Increase Case With Out Statcommentioning
confidence: 99%